Green bonds issuance: Insights in low- and middle-income countries - Ursule Yvanna Otek Ntsama; Yan Chen; Alireza Nasiri; Abdel Hamid Mbouombouo Mboungam (International Journal of Corporate Social Responsibility (JCSR), 2021)
Former reports of Environmental, Social and Governance (ESG) tended to focus on the equity side of investing, and today green bonds also offer and introduce sustainability factors. This paper is about the relevance, potential benefits and key arguments for countries with low-and middle-incomes where financial markets are not comparable with those in developed countries. We begin by stating clearly the relevance of a green economy transformation, highlight the development challenges they face and talk about how a green economy approach can help to solve these challenges. Then an outline of the progress that has been made in this panel, and the economic and social benefits that a green economy can potentially offer to Low- and Middle-Income countries (LMIC's) will be underlined. Finally, we will make recommendations on the range of potential areas for intervention.
Keywords: 650; LMIC's; Green bonds; ESG; Sustainability investment